2008
DOI: 10.1007/s10344-008-0237-0
|View full text |Cite
|
Sign up to set email alerts
|

The non-impact of hunting on moose Alces alces movement, diurnal activity, and activity range

Abstract: Previous studies on moose Alces alces have suggested that interactions with humans may trigger antipredator behaviors and generate a demographical cost. Therefore, we hypothesized that disturbances from small and big game hunting may have negative effects on moose movements, diurnal activity, and activity range. Using location data from 64 moose equipped with GPS collars from three populations (Low Alpine, Inland, Coastal) with different temporal human presence and spatial accessibility, we evaluated the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 45 publications
6
20
0
Order By: Relevance
“…Consequently, our results supported our alternative hypothesis that the rut shaped movement behavior in male moose. Our findings are also in line with previous research that male moose increasingly move around as fall proceeds (Neumann et al ), which may indicate an active search of the area for mating opportunities (Cederlund and Sand , Bubenik ). Surprisingly, regardless of the technological advances in tracking devices during the last decades, the number of studies that specifically focus on movement of male moose during the rut are still limited.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, our results supported our alternative hypothesis that the rut shaped movement behavior in male moose. Our findings are also in line with previous research that male moose increasingly move around as fall proceeds (Neumann et al ), which may indicate an active search of the area for mating opportunities (Cederlund and Sand , Bubenik ). Surprisingly, regardless of the technological advances in tracking devices during the last decades, the number of studies that specifically focus on movement of male moose during the rut are still limited.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to male movement, we found that female moose decreased their movement over time, regardless of hunting activity or rutting period, suggesting that female moose movements were not affected by hunting disturbances on a population scale, supporting earlier research (Neumann et al ). Our findings indicate that female moose did not actively search the area for mating possibilities given the scale of our studies, which is in line with previous reports that female moose primarily feeding during the rut, and do not change their activity ranges during fall (Van Ballerberghe and Miquelle 1996, Neumann et al ). We also found that female moose moved less and crossed roads less often in forests compared to open areas.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies found that human hunting pressure directly influenced large ungulate behavior in terms of movement activity and home ranges size (Root et al 1988, Kilgo et al 1998, in contrast to, Neumann et al (2009) who found no effect on moose movement patterns during hunting season. Several studies found that human hunting pressure directly influenced large ungulate behavior in terms of movement activity and home ranges size (Root et al 1988, Kilgo et al 1998, in contrast to, Neumann et al (2009) who found no effect on moose movement patterns during hunting season.…”
Section: Study Areamentioning
confidence: 99%
“…Because hunting overlaps with the rutting season, a period when males are known to be significantly more active than females (e.g. Cederlund and Sand 1994;Ericsson and Wallin 1996;Neumann et al 2009) and travel over larger areas (Saether et al 2001), they may also expose themselves more often, even when not being disturbed and chased by hunters. For the larger males, such behaviour may have few consequences when faced with naturally occurring predators but can be fatal when faced with human hunters.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, we expected males to be observed relatively more often than females because of their generally higher activity level during the hunting season (e.g. Neumann et al 2009) while we had no specific expectations with regard to the detection probability of females versus calves.…”
Section: Introductionmentioning
confidence: 99%